Modelling and Design of HF 200 kHz Transformers for Hard- and Soft-Switching Application - Radvan, R.; Dobrucky, B.; Frivaldsky, M.; Rafajdus, P. (Elektronika ir Elektrotechnika, 2011)
The paper deals with modelling and design of HF 200 kHz (and more) low-power transformers with determinated leakage induct-ances for both hard- and soft-switching applications. The first group features by small value of the leakage inductance contrary to sec-ond one demanding that value substantially higher. The further aims of the design are minimized weights and dimensions of the trans-formers. Results of numerical simulations and experimental verifications of designed transformers operated in converter circuits are given at the end of the paper. Ill. 13, bibl. 5, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.276